Successful Spontaneous Pregnancy and Live Birth in a Woman With Premature Ovarian Insufficiency and 10 Years of Amenorrhea: A Case Report - Gu, Ying; Xu, Yan (Frontiers in Medicine, 2020)
Background: Primary ovarian insufficiency (POI) is a devastating diagnosis for reproductive-aged women due to the associated infertility and other serious health consequences. Spontaneous pregnancy without hormone replacement therapy (HRT) and/or assisted reproductive technology (ART) rarely occurs in POI patients, particularly in those patients with long-term amenorrhea. Case: On March 4, 2019, a 31-year-old Chinese POI patient visited our hospital for a spontaneous pregnancy after 10 years of amenorrhea and discontinuation of HRT 4 years prior. The patient had menarche at the age of 13, with 3 years of regular menstruation followed by amenorrhea occurring at the age of 20. POI was diagnosed by several hospitals; chromosome examination revealed a normal 46, XX karyotype. Treatment with estradiol valerate and progesterone did lead to resumed menstruation, while amenorrhea resumed after withdrawal of HRT. The patient married at the age of 23 and tried to conceive by HRT until the age of 25; her beta-human chorionic gonadotropin (HCG), estrogen (E2), and progesterone levels were 32987.7 119151.4 mIU/ml, 671.0 >1,000 pg/mL, and 6.6 27.9 ng/ml, respectively. On March 22, 2019, ultrasonography showed an intrauterine pregnancy with a normally developed gestational sac sized 45 × 42 × 32 mm with a 17 mm crown-rump length. On October 29, a 3,400 g healthy girl baby was delivered; the patient had a spontaneous delivery with natural labor. Conclusion: Spontaneous pregnancy is possible in women with POI and 10 years of amenorrhea.